QUALITATIVE PHYTOCHEMICAL SCREENING OF GNIDIA GLAUCA (FRESEN) GILG. PLANT EXTRACT - SANJAY S. KHARAT; PRADEEP B. KUMKAR; SIDDHESH R. RAJPURE; KISHOR S. SONAWANE (International Journal of Pharma and Bio Sciences, 2013)
The present study was undertaken to find out the phytochemicals present in plant Gnidia glauca belonging to the family Thymelaeaceae. Plant extract of dried leaves, bark and stem was prepared and qualitative phytochemical analysis was performed for the presence of Flavonoids, Quinone, Steroids, Tannin, Alkaloids, Phlobatanins, Anthrequinones, Glycosides, Terpenoides, Saponins using standard procedures. Phytochemicals from this plant, Gnidia glauca shows more potential in drug design and it requires further study.